Influence of event managers’ leadership styles and their effects on event management performance in the activities of BRAC - Rahman, K. M. Shakib (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.